2018
DOI: 10.1051/bioconf/20181100021
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships betweenChondrillaL. species in European Russia based on plastid DNA sequencing

Abstract: The article examines the genetic diversity in 54 populations of 9 Chondrilla species (C. acantholepis, C. ambigua, C. brevirostris, C. canescens, C. graminea, C. juncea, C. laticoronata, C. latifolia, and C. pauciflora) in European Russia. Plastid DNA segments trnT–trnF are selected as markers. Reconstruction of evolutionary networks based on the principle of maximum parsimony reveals that the sample is divided into four groups, where group 1 is C. ambigua, 2 – C. brevirostris, 3 – C. laticoronata, 4 – C. acan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The research started with examining the populations of those taxa that had been proved independent species by the earlier research on their morphological variability; and of those two taxa (C. canescens and C. juncea) the independance of which has not yet been established [1].…”
Section: Object Of Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The research started with examining the populations of those taxa that had been proved independent species by the earlier research on their morphological variability; and of those two taxa (C. canescens and C. juncea) the independance of which has not yet been established [1].…”
Section: Object Of Studymentioning
confidence: 99%
“…The research on genetic polymorphism and morphological variability of a number of Chondrilla species in European Russia [1] requires a thorough examination of the species' kariotypic variability.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present study was to assess the boundaries and relationships of Chondrilla species distributed in southern Russia based on biogeographic patterns of their population genetic structure. Some preliminary results of our studies, based on ISSR (Kashin et al 2017) and plastid markers, have been reported and published at the Russian Botanical Society Congress (Kashin et al 2018b). Below we present the final results of our investigations into population genetic structure of Chondrilla populations in southern European Russia.…”
Section: Introductionmentioning
confidence: 99%